Evolution of marine gravel dunes on the open shelf under multi-directional currents conditions - Ribó, Marta; Watson, Sally J.; Macdonald, Helen; Strachan, Lorna J. (Frontiers in Earth Science, 2022)
On inner continental shelves, a variety of coarse grained bedforms, such as gravel dunes, are shaped by hydrodynamic and morphodynamic processes. The formation and evolution of such features reflects a balance between seabed and coastal morphology, sediment type and availability, and regional hydrodynamics. Yet, observing bedform evolution directly in the marine environment is rare, mostly due to the lack of repeated seafloor mapping surveys. In this study we use repeat bathymetry from 3 surveys over 4 years from the western Cook Strait / Te Moana-o-Raukawakawa region, New Zealand / Aotearoa. We integrate the seabed morphology characterisation with sediment classification, and regional hydrodynamic modelling to investigate the evolution of gravel dunes under multi-directional current conditions. The repeat seafloor mapping revealed morphological changes to plan-view dune geometry and bifurcation of crestlines, with maximum observed vertical changes up to 3 m at water depths between 60 and 80 m. However, no dune migration was detected. On our hydrodynamic model we show that the most prominent morphological changes over the gravel dunes are spatially correlated with eddy formation, and high multi-directional near-bottom currents, reaching maximum speeds of ~4 m s-1 and bottom stress of > 25 N m-2 in each tidal cycle. We demonstrate that the average hydrodynamic conditions in this region are capable of mobilising coarse-grained sediment (i.e., sand to gravel), indicating that the observed morphological changes over multi-year time scales are a result of continuous remobilisation by currents, rather than extreme or storm events. Our findings demonstrate the highly dynamic nature of the seabed in the Cook Strait, and need for regular, repeat mapping surveys to ensure up-to-date seabed morphology information.